PENINGKATAN EFIKASI DIRI MELALUI PELATIHAN ORIENTASI MASA DEPAN PADA NARAPIDANA REMAJA - Nurul Husnul Magfirah; Asniar Khumas; Dian Novita Siswanti (Jurnal Psikologi TALENTA, 2018)
The purpose of this study was to examine the effectiviness of future orientation their to improve self-efficacy a prisoner. Self-efficacy is an individual's belief in the ability to solve a problem in a particular situation. Research respondents were selected using purposive sampling technique using experimental design pretest-posttest control group design. Subjects were 20 juvenile inmates from class II A, Maros corretional prison. This study uses a self-efficacy scale based on the theory of Bandura. The results of this study indicate that future orientation training is effective in improving self-efficacy in juvenile inmates with a significance of 0.003. The results showed that future orientation training was considered effective to improve self-efficacy in adolescent inmates in Class II.A Maros Correctional Institution.